Rwanda, La Vie Après - Dervaux, Benoît; Versaille, André (Belgium : Wallonie Image Production, 2014)
Six Tutsi women, raped by Hutu men during the genocide in Rwanda in April,1994, tell their stories of abuse, pregnancy and childbirth. 20 years later, we follow these women and their children, who are now young adults.
Verzio Film Festival Submission
Keywords: Documentary films